Samakālīna kavitā meṃ chanda - Vatsyayan, Sachchidanand Hiranand, 1911- (Vatsala Nidhi prakāśana mālā, 1987)
On the problems of versification in contemporary poetry, with special reference to Hindi poetry; selected papers presented at a workshop of writers organized by Vatsala Nidhi.